Caenorhabditis elegans AF4/FMR2 Family Homolog affl-2 Regulates Heat-Shock-Induced Gene Expression. Issue 4 (1st August 2020) - Walton, Sophie J; Wang, Han; Quintero-Cadena, Porfirio; Bateman, Alex; Sternberg, Paul W
Abstract: To mitigate the deleterious effects of temperature increases on cellular organization and proteotoxicity, organisms have developed mechanisms to respond to heat stress. In eukaryotes, HSF1 is the master regulator of the heat shock transcriptional response, but the heat shock response pathway is not yet fully understood. From a forward genetic screen for suppressors of heat-shock-induced gene expression in Caenorhabditis elegans, we found a new allele of hsf-1 that alters its DNA-binding domain, and we found three additional alleles of sup-45, a previously molecularly uncharacterized genetic locus. We identified sup-45 as one of the two hitherto unknown C. elegans orthologs of the human AF4/FMR2 family proteins, which are involved in regulation of transcriptional elongation rate. We thus renamed sup-45 as affl-2 (AF4/FMR2-Like). Through RNA-seq, we demonstrated that affl-2 mutants are deficient in heat-shock-induced transcription. Additionally, affl-2 mutants have herniated intestines, while worms lacking its sole paralog ( affl-1 ) appear wild type. AFFL-2 is a broadly expressed nuclear protein, and nuclear localization of AFFL-2 is necessary for its role in heat shock response. affl-2 and its paralog are not essential for proper HSF-1 expression and localization after heat shock, which suggests that affl-2 may function downstream of, or parallel to, hsf-1 . Our characterization of affl-2 provides insights into the regulation of heat-shock-induced gene expression to protect against heat stress.